2022
DOI: 10.3390/polym14193991
|View full text |Cite
|
Sign up to set email alerts
|

Production and Assessment of Poly(Lactic Acid) Matrix Composites Reinforced with Regenerated Cellulose Fibres for Fused Deposition Modelling

Abstract: Additive manufacturing can be a valuable tool to process polymeric composites reinforced with bio-based fibres, extending their use and opening new opportunities for more environmentally friendly materials. In this work, poly(lactic acid) (PLA) composites reinforced with regenerated cellulose fibres (lyocell) were processed into novel filaments and used for 3D printing. The Young’s modulus of the filaments increased with the addition of fibres, but substantial porosity was observed in formulations with 20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The voids were generated by the incompatibility between the filler and the polymeric matrix, thus hindering polymer diffusion to complete fill the spaces between layers. Also, the filler may be displaced during deposition of the molten material caused by shear forces of the printing nozzle, thus impairing the deposition in some points (orange ellipse) 17,65,66 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The voids were generated by the incompatibility between the filler and the polymeric matrix, thus hindering polymer diffusion to complete fill the spaces between layers. Also, the filler may be displaced during deposition of the molten material caused by shear forces of the printing nozzle, thus impairing the deposition in some points (orange ellipse) 17,65,66 …”
Section: Resultsmentioning
confidence: 99%
“…Also, the filler may be displaced during deposition of the molten material caused by shear forces of the printing nozzle, thus impairing the deposition in some points (orange ellipse). 17,65,66 Balla et al (2020) 18 developed composites for 3D FDM printing using thermoplastic copolyester (TPC) and soybean shell fibers. The authors evaluated the morphology of the samples printed by SEM and identified that the high viscosity of the TPC produced a displacement or improper connection between the grains of the soybean shell fiber and the polymer matrix.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…In 2022, Gauss et al [ 180 ] explored the use of regenerated cellulose fibers (lyocell) in additive manufacturing to process poly(lactic acid) (PLA) composites for 3D printing. Composite filaments of PLA reinforced with lyocell fibers were successfully produced for fused deposition modelling.…”
Section: Pharmaceutical Applications Of Cellulose-based Textilesmentioning
confidence: 99%
“…It is one of the most versatile biopolymers found in nature. Its use is now moving from sustainability-oriented development to technical solutions for a wide range of applications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, nanocellulose was used as reinforcing material, with the content varying between 1 and 40%. Improvements of up to 84% in tensile strength [ 22 ] and 190% in stiffness were reported [ 8 ]. In some cases, the addition of cellulose had no positive effect on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%